PENGENALAN PERBANKAN SYARIAH MELALUI BIMBINGAN BELAJAR MURID SEKOLAH DASAR DAN SEKOLAH MENENGAH PERTAMA DI DESA GUNUNG BUNDER II, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Shinta Suhartini; Tubagus Rifqy Thantawi; Azizah Mursyidah (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2021)
Abstrack During the Covid-19 pandemic in Indonesia, many sectors of life were suddenly paralyzed. The education sector is no exception, which must experience distance learning (PJJ) or online. In general, tutoring has been considered to reduce students' playing time, but it has been proven that tutoring can provide benefits to children's learning processes. During the current COVID-19 pandemic, students are not getting enough education from teachers, because they have to do online learning. So that in this case tutoring activities can be carried out while still carrying out adequate health protocols. In the implementation of tutoring in the village of Gunung Bunder 2 by applying the question and answer method, guiding students in the learning process, and explaining to parents what is taught to students. The results were quite satisfactory, the students understood the material better and even the enthusiasm of the students was very high. Keywords: tutoring, covid-19 pandemic